A Rapid Machine Computation Method of Conversion Between Lambert Grid and Spherical Co-ordinates - Bahattacharji, J. C. (The International Hydrographic Review, 2015)
An attempt has been made to modify the existing formulae of conversion between Lambert grid and spherical co-ordinates and to design corresponding machine forms of computation, which are much simpler and less time-consuming than others, without requiring the use of elaborate trigonometrical tables (except for some listed values of grid constants and a special table of S1 similar to N1K of Survey of India or y' of U.S.C. & G.S.). The suggested method of conversion, being significantly rapid and economical, is likely to prove of immense value to the surveying profession.